Faktor-Faktor yang Berhubungan dengan Massa Otot, Kekuatan Otot, dan Performa Fisik pada Lansia - Riviati, Nur; Indrajaya, Taufik; Chodilawati, Rukiah; Dibyantari, Ridzqie; Indra, Bima (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Despite its high prevalence and significant impact on health, comprehensive studies are still needed to explore the factors affecting sarcopenia parameters, such as muscle mass, muscle strength, and physical performance. This study aimed to identify the factors influencing sarcopenia parameters in the elderly, including muscle mass, muscle strength, and physical performance. Methods. A cross-sectional study was conducted from July to December 2022 on elderly individuals (>60 years old) at the Geriatric Polyclinic, Moh. Hoesin General Hospital, Palembang, selected through consecutive sampling. Muscle mass was measured using bioimpedance analysis, expressed in ASMI values; muscle strength was measured using a handheld dynamometer; and physical performance was assessed using the five-time sit-to-stand test. The SARC-F score was classified as normal (<4) and abnormal (≥4). Data on age, gender, serum albumin levels, comorbidities, and Mini Nutritional Assessment Short Form (MNA-SF) scores were collected for correlation analysis and comparison with muscle mass, muscle strength, and physical performance. Results. Of the 41 subjects, the average age was 70.75 (SD 7) years, with 56.1% being female. All subjects had low muscle mass, with an average ASMI of 3.31 (SD 0.59) kg/m² in females and 4.89 (SD 1.06) kg/m² in males. The average muscle strength for females was 16.9 (SD 6.1) kg and for males 27.5 (SD 8.3) kg. The five-time sit-to-stand test result for females was 24.2 (SD 14.2) seconds and for males, 21.8 (SD 11.1) seconds. Based on SARC-F, 8 subjects (19.5%) were categorized as at risk for sarcopenia. Serum albumin levels for all subjects were within the normal range [4.3 (SD 0.3) g/dl]. Malnutrition was found in 14 subjects (34.1%) according to the MNA-SF results. Comorbidities were present in 35 patients. Statistical analysis showed a significant correlation between serum albumin levels and muscle strength (r=0.35; p=0.005) and physical performance (r=-0.5; p<0.001). Nutritional status had no significant effect on the three parameters, but it did significantly affect muscle mass in elderly males (p=0.002). Comorbidities, including cardiovascular disease, non-insulin-dependent diabetes mellitus, and musculoskeletal disorders, were not significantly related to any of the sarcopenia parameters. Conclusions. Serum albumin is significantly associated with muscle strength and physical performance, while nutritional status is significantly associated with muscle mass in elderly males. Comorbidities were not significantly related to muscle mass, muscle strength, or physical performance in the elderly.